2003
DOI: 10.1359/jbmr.2003.18.10.1725
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Calcium Transporter Genes Are Upregulated by Estrogens and the Reproductive Cycle Through Vitamin D Receptor-Independent Mechanisms

Abstract: ABSTRACT1␣,25(OH) 2 -vitamin D strongly regulates the expression of the epithelial calcium channel CaT1. CaT1 expression is reduced in ERKO␣ mice and induced by estrogen treatment, pregnancy, or lactation in VDR WT and KO mice. Estrogens and vitamin D are thus independent potent regulators of the expression of this calcium influx mechanism, which is involved in active intestinal calcium absorption.Introduction: Active duodenal calcium absorption consists of three major steps: calcium influx into, transfer thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
147
4
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(163 citation statements)
references
References 60 publications
(131 reference statements)
11
147
4
1
Order By: Relevance
“…This lack of age-dependent differences is in accordance with findings --gained with identical study design and methodology --in cattle and goat (Riner, 2006;Singer, 2006) and several other reports (Kinyamu et al, 1997;Wood et al, 1998;Lee et al, 2003;Pazianas et al, 2003;Yamagishi et al, 2006) and in contrast to data published elsewhere (Horst et al, 1990;Ebeling et al, 1992;Liang et al, 1994;Bischoff et al, 2001;Duque et al, 2002;Holick, 2003). Since an age and/or estrogen dependent impairment of calcium resorption was detectable in elder subjects in numerous studies, a resistance to vitamin D was postulated (Kinyamu et al, 1997;Wood et al, 1998) and furthermore vitamin D-dependent (Kinyamu et al, 1997;Liel et al, 1999;Schwartz et al, 2000;Leonard et al, 2001;Duque et al, 2002;Gilad et al, 2005) and independent effects of estrogens on calcium resorption were verified (Colin et al, 1999;Eisman, 2001;Van Cromphaut et al, 2003). Thus, in future studies hormone-and age-associated effects on calcium and vitamin D metabolism in sheep should be re-examined also in senescent dams with and without hormone substitution and evaluated separately.…”
Section: Resultsmentioning
confidence: 95%
“…This lack of age-dependent differences is in accordance with findings --gained with identical study design and methodology --in cattle and goat (Riner, 2006;Singer, 2006) and several other reports (Kinyamu et al, 1997;Wood et al, 1998;Lee et al, 2003;Pazianas et al, 2003;Yamagishi et al, 2006) and in contrast to data published elsewhere (Horst et al, 1990;Ebeling et al, 1992;Liang et al, 1994;Bischoff et al, 2001;Duque et al, 2002;Holick, 2003). Since an age and/or estrogen dependent impairment of calcium resorption was detectable in elder subjects in numerous studies, a resistance to vitamin D was postulated (Kinyamu et al, 1997;Wood et al, 1998) and furthermore vitamin D-dependent (Kinyamu et al, 1997;Liel et al, 1999;Schwartz et al, 2000;Leonard et al, 2001;Duque et al, 2002;Gilad et al, 2005) and independent effects of estrogens on calcium resorption were verified (Colin et al, 1999;Eisman, 2001;Van Cromphaut et al, 2003). Thus, in future studies hormone-and age-associated effects on calcium and vitamin D metabolism in sheep should be re-examined also in senescent dams with and without hormone substitution and evaluated separately.…”
Section: Resultsmentioning
confidence: 95%
“…The increased Ca absorption is thought to be the reason for the hypercalciuria that is observed during pregnancy. Some investigators have suggested that Ca absorption during pregnancy is not dependent on vitamin D, since intestinal Ca transport genes are up regulated by oestrogens, which are increased Proceedings of the Nutrition Society during pregnancy (5) . However, severe vitamin D deficiency with secondary hyperparathyroidism during pregnancy has been shown to lead to abnormal neonatal Ca homoeostasis.…”
Section: Fetal Ca Demands During Pregnancymentioning
confidence: 99%
“…Nonspecific blockage with ruthenium red, Gd 3+ , and La 3+ was observed (19). TRPV6 mRNA expression is regulated by dietary calcium, 1,25-vitamin D3, dihydrotestosterone, and estrogen (20)(21)(22). The intestinal calcium absorption is significantly reduced in TRPV6 knockout mice (23).…”
Section: Introductionmentioning
confidence: 97%